Effects of tart cherry juice supplementation on recovery from exercise-induced muscle damage in athletes: A systematic review and meta-analysis - Daab, W.; Bouzid, M. A.; Nassis, G. P.; Arumugam, A.; Ammar, A.; Pojskic, H.; Abaïdia, A.-E. (Sports Medicine - Open, 2026)
Background Exercise-induced muscle damage (EIMD) is known to impair neuromuscular performance, provoke inflammation, and delay recovery. Tart cherry (TC) juice, a polyphenol-rich nutritional product, has been proposed as a strategy to support recovery in athletes; however, findings across studies remain inconsistent.